L-Shell X-Ray Conversion Yields for Laser-Irradiated Tin and Silver Foils. (7th June 2022) - Singh, R.L.; White, S.; Charlwood, M.; Keenan, F.P.; Hyland, C.; Bailie, D.; Audet, T.; Sarri, G.; Rose, S. J.; Morton, J.; Baird, C.; Spindloe, C.; et al.
Abstract : We have employed the VULCAN laser facility to generate a laser plasma X-ray source for use in photoionization experiments. A nanosecond laser pulse with an intensity of order 10 15 Wcm −2 was used to irradiate thin Ag or Sn foil targets coated onto a parylene substrate, and the L-shell emission in the 3.3–4.4 keV range was recorded for both the laser-irradiated and nonirradiated sides. Both the experimental and simulation results show higher laser to X-ray conversion yields for Ag compared with Sn, with our simulations indicating yields approximately a factor of two higher than those found in the experiments. Although detailed angular data were not available experimentally, the simulations indicate that the emission is quite isotropic on the laser-irradiated side but shows close to a cosine variation on the nonirradiated side of the target as seen experimentally in the previous work.